Assessment of Gaps in Care and the Development of a Care Pathway for Anemia in Patients with Inflammatory Bowel Diseases. Issue 1 (January 2017) - Hou, Jason K.; Gasche, Christoph; Drazin, Noam Z.; Weaver, Sarah Alandra; Ehrlich, Orna G.; Oberai, Ridhima; Zapala, Sophie; Siegel, Corey A.; Melmed, Gil
Abstract : Background: Anemia is a common complication among patients with inflammatory bowel diseases (IBD) and is associated with high rates of IBD-related complications, resource utilization, and impaired quality of life. Despite practice guidelines for anemia in patients with IBD, gaps remain in the perceptions of anemia among health care providers. The aims of this study were to identify gaps in care and to develop a care pathway for anemia in patients with IBD. Methods: The Crohn's & Colitis Foundation of America anemia care pathway was developed by a committee using principles of cognitive task analysis. Focus groups of providers of patients with IBD were performed to identify domains of perceptions and management decisions for anemia and IBD. Knowledge elicitation from subject experts in anemia was conducted using case-based scenarios of patients with IBD and anemia to determine decision-making branch points. The care pathway was modified in an iterative fashion to encompass clinical presentations of anemia in IBD and potential barriers to the recognition, management, and follow-up of anemia. Results: Variations were observed in how providers define iron deficiency, thresholds for treatment of anemia, and route of iron therapy. A care pathway for anemia incorporating the World Health Organization definition of anemia, universal hemoglobin and ferritin screening, evaluation of iron stores using ferritin and transferrin saturation, management of anemia based on adequacy of iron stores, and follow-up was developed. Conclusions: The authors identified domains of how providers perceive and manage patients with IBD and anemia, and developed a care pathway to align clinical practices with guideline recommendations. Abstract : Article first published online 30 September 2016.